Public engagement and education developing and fostering stewardship for an archaeological future - Erdman, Katherine (Katherine M.) (Berghahn Books, 2019)
"The world's collective archaeological heritage is threatened by war, development, poverty, climate change, and ignorance. To protect our collective past, archaeologists must involve the general public through interpersonal experiences that develop an interest in the field at a young age and foster that interest throughout a person's life. Contributors to this volume share effective approaches for engaging and educating learners of all ages about archaeology and how one can encourage them to become stewards of the past. They offer applied examples that are not bound to specific geographies or cultures, but rather, are approaches that can be implemented almost anywhere"--